Endoscopic ultrasound-guided pancreatic fluid collections' transmural drainage outcomes in 100 consecutive cases of pseudocysts and walled off necrosis: a single-centre experience from the United Kingdom. (4th May 2018) - Shekhar, Chander; Maher, Ben; Forde, Colm; Mahon, Brinder Singh
Abstract: Background and aim: Endoscopic ultrasound-guided drainage is a minimally invasive first-line modality for the drainage of pancreatic fluid collection (PFC) resulting in a shorter hospital stay and less morbidity compared with surgical cystogastrostomy. Our aim is to evaluate potential differences in the outcomes of endoscopic ultrasound (EUS) guided transmural drainage (EUS-TD) drainage of pancreatic pseudocyst (PP) and walled-off necrosis (WON). Method: We retrospectively reviewed 100 consecutive EUS-guided drainages of PFC utilising EUS reports; clinical notes and imaging with follow-up (FU) to 12 months. All procedures were undertaken under conscious sedation with EUS guidance alone (without fluoroscopy) and placement of plastic double pigtail stents. Results: In these 100 sequential cases, there were 78 cases of PP and 22 cases of WON. All 22/22(100%) cases of WON had successful EUS-guided stent placement. In 2/22(9%), there was little or no clinical improvement. These two patients required further computed tomography (CT)–guided drainage and one of these patients (1/22) (4.5%) developed recurrence within 12 months FU after removal of stents. In case of PP, overall stent placement was successful in 76/78 (97%) patients, but 6/78(8%) required 2nd EUS procedure after failure to show clinical improvement; 3/78(2.5%) required further CT-guided drainage. The overall complication rate was 9%(9/100) with 4%(4/100) requiring endoscopic or CT-guided intervention with no overall 30-day mortality. Conclusion: This is the largest series from a single UK centre demonstrating that EUS-guided cystogastrostomy of PFC drainage using plastic double pigtail stents is sufficient in majority of cases with PFC including that of WON, with or without infection.